2011
DOI: 10.1016/j.psyneuen.2011.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Poorer self-rated health is associated with elevated inflammatory markers among older adults

Abstract: Objective Self-rated health is a strong independent predictor of mortality after accounting for objective health status, behavioral risk factors, and sociodemographic characteristics. However, mechanisms underlying this association are largely unexplained. Inflammation has been associated with increased risk of morbidity and mortality in the elderly. The current study aimed to: 1) examine associations between self-rated health and serum inflammatory markers in older adults; 2) examine the relative strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
152
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(182 citation statements)
references
References 50 publications
26
152
0
4
Order By: Relevance
“…Our results are in line with Christian et al (2011), who reported similar results with the only significant self-rated health component, physical functioning. Moreover, a recent review by Singh and Newman (2011), based on the results from major epidemiologic studies, showed IL-6 to be robustly associated with physical functioning in older adults.…”
Section: Inflammatory Associations With Individual Aspects Of Functiosupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in line with Christian et al (2011), who reported similar results with the only significant self-rated health component, physical functioning. Moreover, a recent review by Singh and Newman (2011), based on the results from major epidemiologic studies, showed IL-6 to be robustly associated with physical functioning in older adults.…”
Section: Inflammatory Associations With Individual Aspects Of Functiosupporting
confidence: 93%
“…However, this study is the first to show the additional significance of IL-6 as a global functioning marker in the oldest old. Only a few studies have reported that poorer global self-rated health is associated with elevated inflammatory markers among older adults (Christian et al 2011;Cohen et al 1997). Christian et al (2011) reported IL-6 and CRP to be associated with self-rated health in a relatively healthy study population with caregiving responsibilities with a mean age of 63.8 years, which is in line with our results in the community-dwelling oldest old, even with high comorbidity.…”
Section: Il-6 As Marker Of Global Functioning In Very Old Personssupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, IL-6 could simply be an indicator of biological frailty or immunosenescence in general, in which IL-6 is likely to represent a general down-spiral pathway involving multiple pathophysiological mechanisms and therefore reflects the associated patient's global function (Penninx et al 2004). Only two previous studies have reported that poorer self-rated global health is associated with elevated IL-6 levels in older adults (Christian et al 2011;Cohen et al 1997). We showed a clear dose-response relationship of global functional decline with increasing serum levels of baseline IL-6.…”
Section: Gds Decline N=316mentioning
confidence: 99%
“…Only poor self-rated global health has been previously associated with elevated inflammatory markers in older persons (Christian et al 2011;Cohen et al 1997). Different sets of inflammatory markers have been measured in studies with diverse assays and in various settings, disabling inflammatory marker comparability between various studies.…”
Section: Introductionmentioning
confidence: 99%